The Effect Of Facilities And Service Quality On Consumer Satisfaction In Algifari Housing Residents In Enrekang District - ., Zarina; Danindra, Fuad; Setiawan, Dedi; Nasrul, Muhammad; Kamil, Ahmad (CV. ITTC INDONESIA, 2025)
This study was conducted to determine the effect of facilities and service quality onconsumer satisfaction at Al gifari Residential housing in Enrekang Regency. Respondents in thisstudy were 109, the researcher's data collection process was to conduct observations by givingquestionnaires directly to respondents. Based on the results of the analysis obtained, it shows thatthe facility variable has a significant effect on consumer satisfaction as shown in the pvalue4,507(<0.05), while the analysis results for the service quality variable have a significanteffect on consumer satisfaction as shown in the p-value.4,204(< 0.05). The results of thesimultaneous analysis show that facilities and service quality have an effect on ConsumerSatisfaction with a value of 63.294 > 3.08.Keywords: Facilities, service quality, customer satisfaction